Self-reported music perception is related to quality of life and self-reported hearing abilities in cochlear implant users. (2nd January 2022) - Fuller, Christina; Free, Rolien; Maat, Bert; Başkent, Deniz
Abstract : Objectives: To investigate the relationship between self-reported music perception and appreciation and (1) quality of life (QoL), and (2) self-assessed hearing ability in 98 post-lingually deafened cochlear implant (CI) users with a wide age range. Methods: Participants filled three questionnaires: (1) the Dutch Musical Background Questionnaire (DMBQ), which measures the music listening habits, the quality of the sound of music and the self-assessed perception of elements of music; (2) the Nijmegen Cochlear Implant Questionnaire (NCIQ), which measures health-related QoL; (3) the Speech, Spatial and Qualities (SSQ) of hearing scale, which measures self-assessed hearing ability. Additionally, speech perception was behaviorally measured with a phoneme-in-word identification. Results: A decline in music listening habits and a low rating of the quality of music after implantation are reported in DMBQ. A significant relationship is found between the music measures and the NCIQ and SSQ; no significant relationships are observed between the DMBQ and speech perception scores. Conclusions: The findings suggest some relationship between CI users' self-reported music perception ability and QoL and self-reported hearing ability. While the causal relationship is not currently evaluated, the findings may imply that music training programs and/or device improvements that improve music perception may improve QoL and hearing ability.